Essential Oil Content and Components in Different Purple Basil Genotypes According to the Diurnal Changes (Bangladesh Journal of Botany, 2023)
In the present study the diurnal variations in plant parts of different purple basil genotypes were determined. Three different purple basil genotypes (Arapgir, Piros and Midnight) were used as plant material. Plants were harvested at 06:00, 12:00, 18:00 and 00:00 hrs to determine the diurnal variation within a day at harvesting time. Essential oil ratio among genotypes, harvesting times and parts of plant varied between 0.46- 0.95%, 0.60 to 0.92% and 0.14-1.29%, respectively. Essential oil ratios among the triple interactions were found to range from 0.05 to 2.57%. The major essential oil was linalool in all genotypes. Results showed that the higher essential oil ratio can be obtained from dry flowers of Arapgir genotype harvested at 00:00 and also, Midnight genotype contained higher essential oil content than others.Bangladesh J. Bot. 52(2): 357-367, 2023 (June)